Principles of Ethical Speaking According to the Prophet's Hadith: An Analysis of Kutub Al-Tis`Ah - Masruroh (Taqriri: Journal of Al-Hadith Science Studies, 2025)
This study aims to analyze the concept of speaking ethics in the perspective of the hadith of the Prophet Muhammad SAW through a library research approach. Speaking ethics is an important part of social ethics in Islam which functions as a guideline for a Muslim's communicative behavior. The research data sources were obtained from several primary hadith books, namely: Ṣaḥīḥ Būkhārī, Ṣaḥīḥ Muslim, Sunan al-Tirmidhī, Sunan Abū Dāud and Sunan Ibn Mājah. The results of the study indicate that speaking ethics in the hadith include several basic principles, including the obligation to speak well or remain silent, speak effectively and not excessively, avoid lying, prioritize older or more knowledgeable people in speaking, avoid useless debates, and prohibition of cursing (backbiting) and finding fault with others. The findings of this study confirm that the quality of a Muslim's verbal communication is related to the quality of his faith. Speech etiquette serves as a moral control mechanism in social interactions and as an effort to maintain harmonious relationships between people, especially among Muslims. Therefore, the communication ethics taught in the hadith can serve as an important reference in establishing civilized and constructive Islamic communication practices within society.